An overview on small molecule-induced differentiation of mesenchymal stem cells into beta cells for diabetic therapy - Nimshitha Pavathuparambil Abdul Manaph (17870420) (2019)
The field of regenerative medicine provides enormous opportunities for generating beta cells from different stem cell sources for cellular therapy. Even though insulin-secreting cells can be generated from a variety of stem cell types like pluripotent stem cells and embryonic stem cells, the ideal functional cells should be generated from patients’ own cells and expanded to considerable levels by non-integrative culture techniques. In terms of the ease of isolation, plasticity, and clinical translation to generate autologous cells, mesenchymal stem cell stands superior. Furthermore, small molecules offer a great advantage in terms of generating functional beta cells from stem cells. Research suggests that most of the mesenchymal stem cell-based protocols to generate pancreatic beta cells have small molecules in their cocktail. However, most of the protocols generate cells that mimic the characteristics of human beta cells, thereby generating “beta cell-like cells” as opposed to mature beta cells. Diabetic therapy becomes feasible only when there are robust, functional, and safe cells for replacing the damaged or lost beta cells. In this review, we discuss the current protocols used to generate beta cells from mesenchymal cells, with emphasis on small molecule-mediated conversion into insulin-producing beta cell-like cells. Our data and the data presented from the references within this review would suggest that although mesenchymal stem cells are an attractive cell type for cell therapy they are not readily converted into functional mature beta cells. Other Information Published in: Stem Cell Research & Therapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s13287-019-1396-5